Uji aktivitas antipiretik ekstrak etanol daun kembang merak (Caesalpinia pulcherrima (L.) terhadap mencit jantan (Mus musculus) yang diinduksi vaksin DPT-HB - Handayana, Icha; Mambang, D. Elysa Putri; Nasution , M. Pandapotan; Rahayu , Yayuk Putri (Journal of Pharmaceutical and Sciences, 2024)
Peacock flower leaves are an ornamental plant Indonesian people use to decorate their yards. Peacock flower leaves contain alkaloids, saponins, tannins, glycosides, and calcium oxalate. Peacock flower leaves are often used as an antipyretic, antibacterial, and liver inflammation. Fever is common in children and adults. The use of paracetamol at this time is usually found in the community, but the use of paracetamol has adverse side effects. The research aims to determine the antipyretic activity of the ethanol extract of peacock flower leaves. This study was experimental; the research method was carried out by screening phytochemicals and administering a suspension of peacock flower leaf extract given orally at a dose of 50,100,200mg/kg in male mice induced with DPT-HB. Paracetamol was used as a comparison, and then the body temperature of the mice was measured using a thermometer every 30 minutes for 3 hours (180 minutes) rectally. Data were analysed using SPSS ver.24 One Way ANOVA and continued with the Tukey test. The results of the phytochemical screening of simplicia powders and extracts contained secondary metabolites of alkaloids, flavonoids, tannins, saponins, triterpenoids/steroids and glycosides. The antipyretic activity obtained in each treatment significantly affected the One-way ANOVA and Tukey test results with a P <0.05. The results showed that peacock flower leaf extract had antipyretic activity, and the greatest antipyretic activity was at a dose of 100mg/kg BW with a very significant difference with 1% Paracetamol. It can be concluded that peacock flower leaf extract has the most effective antipyretic activity at a dose of 100mg/kg BB.